Subacute Disseminated Intravascular Coagulation in a Patient with Liver Metastases of a Renal Cell Carcinoma - L. C. van der Wekken; R. J. L. F. Loffeld (Case Reports in Oncological Medicine)
Disseminated intravascular coagulation (DIC) is a syndrome characterised by simultaneous bleeding and thromboembolic formation. Its acute form is associated with severe bacterial infections and hematological malignancies. It has a fulminant presentation with prolonged bleeding times and diffuse thrombosis. On the other hand, chronic DIC can be asymptomatic for long periods of time and can be seen in patients with disseminated malignancies. This case report describes a patient who developed DIC within one week and bled profusely from venipuncture wounds. An underlying hepatogenic metastasised renal cell carcinoma appeared to be the cause. This is an uncommon and diagnostically challenging presentation.